2021
DOI: 10.1073/pnas.2108534118
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal neurons’ cytosolic and membrane-bound ribosomal transcript profiles are differentially regulated by learning and subsequent sleep

Abstract: The hippocampus is essential for consolidating transient experiences into long-lasting memories. Memory consolidation is facilitated by postlearning sleep, although the underlying cellular mechanisms are largely unknown. We took an unbiased approach to this question by using a mouse model of hippocampally mediated, sleep-dependent memory consolidation (contextual fear memory). Because synaptic plasticity is associated with changes to both neuronal cell membranes (e.g., receptors) and cytosol (e.g., cytoskeleta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(67 citation statements)
references
References 87 publications
(201 reference statements)
8
59
0
Order By: Relevance
“…Across species, biochemical [ 8 , 49–52 ], transcriptomic [ 6 , 53 ], and ribosome profiling [ 8 , 11 ] data suggest that protein translation/quality control and transport are affected by acute sleep loss. For example, in nematodes, Drosophila , and mice [ 49 , 51 ], a brief period of SD leads to an enhanced unfolded protein response (UPR; the cellular stress response to accumulation of misfolded protein in the ER lumen) ( Figure 1 ).…”
Section: Sleep Deprivation Cellular Energetics and Mitochondrial Func...mentioning
confidence: 99%
See 2 more Smart Citations
“…Across species, biochemical [ 8 , 49–52 ], transcriptomic [ 6 , 53 ], and ribosome profiling [ 8 , 11 ] data suggest that protein translation/quality control and transport are affected by acute sleep loss. For example, in nematodes, Drosophila , and mice [ 49 , 51 ], a brief period of SD leads to an enhanced unfolded protein response (UPR; the cellular stress response to accumulation of misfolded protein in the ER lumen) ( Figure 1 ).…”
Section: Sleep Deprivation Cellular Energetics and Mitochondrial Func...mentioning
confidence: 99%
“…Moreover, to date, there is no data on how sleep loss affects the subcellular distribution of the Golgi, ER, lysosomes, or endosomes in neurons. Appropriate subcellular localization and organization of these organelles is essential for spatial regulation of both protein and mRNA, which in neurons plays vital roles in neurotransmission, synaptic plasticity, and information storage [ 8 , 61 , 62 ]. Beyond these essential functions, the presence of Golgi and ER in neurites plays additional roles, including local calcium buffering, regulation of synaptic extracellular glycoproteins, and lipid biogenesis [ 63 , 64 ].…”
Section: Sleep Deprivation Cellular Energetics and Mitochondrial Func...mentioning
confidence: 99%
See 1 more Smart Citation
“…2 ) demonstrate that chemogenetically enhancing cAMP levels at multiple time points during SD can render hippocampal LTP resilient to the impact of 5 hours of acute SD. Other studies have shown that shorter windows of sleep deprivation can also produce alterations in gene expression in the hippocampus (Delorme et al, 2021) and the cortex (Cirelli & Tononi, 2000) and impair memory and synaptic plasticity (Prince et al, 2014). These findings raise a question about whether the enhancement of cAMP levels in the early or late windows of SD have consistent or different effects on the maintenance of LTP.…”
Section: Resultsmentioning
confidence: 99%
“…For example, two members of the MMP family, MMP3 and MMP7, have both been shown to drive activity-dependent changes in synaptic structure ( Bilousova et al, 2006 ; Wójtowicz and Mozrzymas, 2014 ; Aerts et al, 2015 ; Brzdąk et al, 2017 ). Recently, the protease cathepsin-S was suggested to remodel PNNs in a circadian manner, which would presumably allow synapses to be modified during sleep ( Pantazopoulos et al, 2020 ; Delorme et al, 2021 ; Harkness et al, 2021 ). Additional proteases, including neurotrypsin and members of the “a disintegrin and metalloproteinase with TSP motifs” (ADAMTS) family, may also be involved in mediating synaptic plasticity.…”
Section: Remodeling Of the Extracellular Matrix Permits Synaptic Plas...mentioning
confidence: 99%